PENGARUH PENDIDIKAN KESEHATAN TERHADAP PERUBAHAN PERILAKU PERSONAL HYGIENE SISWA SEKOLAH DASAR - Hidayah, Arinil (Jurnal Kesehatan Ilmiah Aufa Royhan, 2020)
School age children are a special group that is vulnerable to health problems. Health problems in school-age children are often related to personal hygiene or personal hygiene including hair hygiene, nail and hand hygiene, skin hygiene, clothing hygiene, oral hygiene, and overall body care. Inability to maintain personal hygiene, a person will easily experience infection (Mukarromah & Menge, 2020). The purpose of this study was to determine whether there is an effect of health education with the lecture method on changes in personal hygiene behavior of elementary school students. The special target in this study is to examine the personal hygiene behavior of students before and after being given health education by using the lecture method. The type of research used was one group pre-test and post-test design without a control group. Sampling in this study was carried out by purposive sampling technique with a total sample of 25 students with data analysis using Paired sample t test. The statistical test results obtained p = 0.000, this shows that statistically there is a significant difference between personal hygiene behavior before and after being given health education with the lecture method. It is hoped that the school can work together with health workers to provide health education about personal hygiene with the continuous lecture method so that students can carry out good personal hygiene actions continuously and become a good culture among the community.